2017
DOI: 10.1158/1078-0432.ccr-17-0101
|View full text |Cite
|
Sign up to set email alerts
|

A Zebrafish Model Discovers a Novel Mechanism of Stromal Fibroblast-Mediated Cancer Metastasis

Abstract: Cancer metastasis can occur at the early stage of tumor development when a primary tumor is at the microscopic size. In particular, the interaction of malignant cells with other cell types including cancer-associated fibroblasts (CAF) in promoting metastasis at the early stage of tumor development remains largely unknown. Here, we investigated the role of CAFs in facilitating the initial events of cancer metastasis when primary tumors were at microscopic sizes. Multicolor-coded cancer cells and CAFs were coimp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 39 publications
3
69
1
Order By: Relevance
“…However, direct, functional assessment of drug responses on primary patient‐derived tumor cells gives the most accurate information on whether the patient will respond to the tested drugs. For example, zebrafish tumor xenograft platforms allow human tumor samples to be grafted into zebrafish embryos, where their growth as primary tumors and their dissemination to distal regions can be determined in the presence or absence of drugs . This platform has been used to demonstrate efficacy of the anti‐PDPN compounds, including MASL on oral squamous cell carcinoma and melanoma xenografts .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct, functional assessment of drug responses on primary patient‐derived tumor cells gives the most accurate information on whether the patient will respond to the tested drugs. For example, zebrafish tumor xenograft platforms allow human tumor samples to be grafted into zebrafish embryos, where their growth as primary tumors and their dissemination to distal regions can be determined in the presence or absence of drugs . This platform has been used to demonstrate efficacy of the anti‐PDPN compounds, including MASL on oral squamous cell carcinoma and melanoma xenografts .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For example, zebrafish tumor xenograft platforms allow human tumor samples to be grafted into zebrafish embryos, where their growth as primary tumors and their dissemination to distal regions can be determined in the presence or absence of drugs. [66][67][68] This platform has been used to demonstrate efficacy of the anti-PDPN compounds, including MASL on oral squamous cell carcinoma and melanoma xenografts. 17,27 This approach can be used to gather critical information that can be reported back to oncologists in charge of treatment planning in less than 5 days after surgery.…”
Section: Podoplanin Car-t Cellsmentioning
confidence: 99%
“…The pro-invasion morphological changes induced in CRC cells upon contact with CAFs supernatant confirm the multi-functional role they play in metastasis [45]. A recent study showed that CAFs were able to induce metastasis at a very early stage in tumor development, even when the tumor was of microscopic size, in a small number of cancer cells which remained associated with CAFs upon entering the circulation, potentially forming micrometastatic niches in distal organs which are only visible upon progression [46]. These mechanisms that induce tumor cell invasion and migration may be an interesting target for novel therapies in order to inhibit metastasis.…”
Section: Cafsmentioning
confidence: 86%
“…Countless studies have shown that homing and extravasation might be more than simply a mechanical response to a faulty environment. TAMs were shown to secrete TNF-α, VEGF and TGF-β into the circulation to distal tissues where they activate tissue macrophage production of S100A8, which is a chemoattractant for CTCs [46]. CTC attachment to the endothelium is allowed by endothelial cell P-and E-selectins binding to tumor cells as well as tumor glycan patterns and adhesion molecule interactions such as integrin and CD44 interactions [73].…”
Section: Active Extravasationmentioning
confidence: 99%
“…In support of this possibility, it has been shown that the concentration of the broad-spectrum MMP inhibitor, MMI270, that was required to reduce the invasion of LECs was 100-fold higher than that required to decrease invasion of Lewis lung carcinoma cells (31). Stromal cells regulate cancer cell invasion and metastasis via multiple mechanisms (32)(33)(34), including MMP-9 modulation (9,35).…”
Section: Discussionmentioning
confidence: 99%